2018
DOI: 10.5539/jas.v10n5p229
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Thermal Time, Phyllochron and Plastochron in Passion Fruit Plants With Irrigation Depth and Hydrogel

Abstract: The passion fruit demands water for its growth and production. Water management is relevant in regions characterized by low rainfall indices, such as semi-arid regions. In this direction, the use of hydrogel in the soil allows the water that is supplied through irrigation to be better utilized by the plants, reducing leach losses. The objective of this experiment was to evaluate the influence of hydrogel in soil cultivated with passion fruit and irrigated to various water depths on the thermal time of the phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The present result is confirmed by the previous work of Kaplan [ 23 ], who found that the application of hydrogel at a moderate concentration gave maximum growth parameters using a level of 500 g∙plant −1 apple ‘Gala Must’ variety. These results concur with those of Awad et al [ 24 ] in the apple seedling and those of Cavalcante et al [ 25 ] in passion fruit. In addition, by increasing the ratio of hydrogel in the substrate’s culture, Hüttermann et al [ 26 ], Akhter et al [ 27 ], and Chirino et al [ 28 ] found increases in shoot height.…”
Section: Resultssupporting
confidence: 93%
“…The present result is confirmed by the previous work of Kaplan [ 23 ], who found that the application of hydrogel at a moderate concentration gave maximum growth parameters using a level of 500 g∙plant −1 apple ‘Gala Must’ variety. These results concur with those of Awad et al [ 24 ] in the apple seedling and those of Cavalcante et al [ 25 ] in passion fruit. In addition, by increasing the ratio of hydrogel in the substrate’s culture, Hüttermann et al [ 26 ], Akhter et al [ 27 ], and Chirino et al [ 28 ] found increases in shoot height.…”
Section: Resultssupporting
confidence: 93%
“…The transplanting of yellow passion fruit seedlings was done on 09/13/2016 when the seedlings had four pairs of fully expanded leaves and height between 23 and 25 cm. The system used to support the plants was a espalier type, with a height of 2.3 m, consisting of a 12 smooth wire installed on top of the stakes (CAVALCANTE et al, 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…is also negatively affected under water deficit, as reported by Souza et al (2018), who found that reduction in stomatal conductance caused a negative effect on plant growth and biomass accumulation. This makes yellow passion fruit dependent, under these conditions, on irrigation in different phenological stages (CAVALCANTE et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%